International Scientific Cooperation in the Arctic among the BRICS Countries - Yaxin Wang (Управленческое консультирование, 2023)
This article summarises the characteristics of the current platform for BRICS scientific research and cooperation in the Arctic. The BRICS countries’ activities for the development of the Arctic region are analysed. The Arctic cooperation platform is explored through an analysis of official documents, a review of ongoing official events. The BRICS countries are implementing relevant joint projects to develop and explore the Arctic, on the one hand realising their own needs, and on the other using the specific advantages of their economic systems. From time to time, they organise and hold multilateral meetings and conferences. However, most cooperation takes place in a bilateral format. It is based on the organisation of conferences, cooperation between research institutes and joint training. This helps the BRICS countries to expand their influence in the Arctic. Based on an analysis of the identified materials, including projects developed to date but not yet implemented, the author seeks to summarise the main characteristics and features of BRICS Arctic cooperation and to identify its strengths and weaknesses. The conclusions of the paper present relevant proposals for improving the effectiveness of the BRICS countries’ joint work on the Arctic agenda in the medium term.